Ectopic bone formation by aggregated mesenchymal stem cells from bone marrow and adipose tissue: A comparative study. (21st August 2017) - Fennema, Eelco M.; Tchang, Laurent A.H.; Yuan, Huipin; van Blitterswijk, Clemens A.; Martin, Ivan; Scherberich, Arnaud; de Boer, Jan
Abstract: Tissue engineered constructs (TECs) based on spheroids of bone marrow mesenchymal stromal cells (BM‐MSCs) combined with calcium phosphate microparticles and enveloped in a platelet‐rich plasma hydrogel showed that aggregation of MSCs improves their ectopic bone formation potential. The stromal vascular fraction (SVF) and adipose‐derived MSCs (ASCs) have been recognized as an interesting MSC source for bone tissue engineering, but their ectopic bone formation is limited. We investigated whether aggregation of ASCs could similarly improve ectopic bone formation by ASCs and SVF cells. The formation of aggregates with BM‐MSCs, ASCs and SVF cells was carried out and gene expression was analysed for osteogenic, chondrogenic and vasculogenic genes in vitro . Ectopic bone formation was evaluated after implantation of TECs in immunodeficient mice with six conditions: TECs with ASCs, TECs with BM‐MSC, TECs with SVF cells (with and without rhBMP2), no cells and no cells with rhBMP2. BM‐MSCs showed consistent compact spheroid formation, ASCs to a lesser extent and SVF showed poor spheroid formation. Aggregation of ASCs induced a significant upregulation of the expression of osteogenic markers like alkaline phosphatase and collagen type I, as compared with un‐aggregated ASCs. In vivo, ASC and SVF cells both generated ectopic bone in the absence of added morphogenetic proteins. The highest incidence of bone formation was seen with BM‐MSCs (7/9) followed by SVF + rhBMP2 (4/9) and no cells + rhBMP2 (2/9). Aggregation can improve ectopic bone tissue formation by adipose‐derived cells, but is less efficient than rhBMP2. A combination of both factors should now be tested to investigate an additive effect.